STUDENT’S PERCEIVED COMPETENCE IN MOCK JOB INTERVIEWS - Salmiza Abdul Rahim; Lam Kok Wei (PUPIL: International Journal of Teaching, Education and Learning, 2025)
With the increasing importance of English proficiency in Malaysia’s competitive job market—particularly in interview settings—this research investigates students’ self-perceptions of their readiness and abilities after participating in simulated job interviews. A total of 36 students took part in the study by completing a self-evaluation questionnaire. The findings reveal that while students generally perceived themselves as prepared, especially in areas such as appearance, non-verbal cues, and basic interview etiquette, there was a noticeable gap in their perceived performance, particularly in spoken grammar, clarity, and fluency. The results underscore the need for targeted instruction in linguistic accuracy, structured speaking, and real-time communication strategies. This study offers practical implications for educators aiming to enhance students’ employability through language training and interview skill development.